Material for printed wiring board and method for manufacturing printed wiring board

The use of a polyimide resin-based adhesive layer in the printed wiring board material addresses the trade-off between adhesion and smoothness, ensuring strong adhesion and high smoothness at the interface, thereby improving high-frequency characteristics.

JP2025056512APending Publication Date: 2025-04-08TOYO ALUMINIUM KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023166031
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In high-frequency applications, printed wiring boards require both high adhesion strength between the copper plating layer and the substrate, and high smoothness at the interface to minimize the skin effect, presenting a trade-off between adhesion and smoothness.

Method used

A printed wiring board material is developed with an adhesive layer containing a specific polyimide resin, which is copolymerized with a bisphenol diether-type acid dianhydride and a diamine compound, applied between the copper plating layer and the substrate, eliminating the need for unevenness at the interface.

Benefits of technology

This solution achieves strong adhesion between the copper plating layer and the substrate while maintaining high smoothness at the interface, enhancing the high-frequency characteristics of the printed wiring board without compromising adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056512000001_ABST
    Figure 2025056512000001_ABST
Patent Text Reader

Abstract

To provide materials for printed wiring boards that can bring about printed wiring boards with sufficient adhesive strength at the interface between a copper plating layer and a substrate without forming unevenness at the interface between the copper plating layer and the substrate, and a method for manufacturing printed wiring boards using the materials for printed wiring boards.SOLUTION: A printed circuit board material 10 comprises at least a catalyst layer 12 and an adhesive layer 13 containing polyimide resin, at least on one side 11a of the metal foil 11, in this order, and the polyimide resin consists of copolymerization of acid dianhydride, including bisphenol diether type acid dianhydride, and diamine compounds.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a material for printed wiring boards and a method for producing a printed wiring board using the same. [Background technology]

[0002] Generally, printed wiring boards such as rigid boards, build-up boards, and flexible printed circuit boards are distributed, which have a catalyst layer on the surface of a base material such as a resin, and further have a copper plating layer in the shape of a circuit pattern on the surface. As the processing speed of electronic components such as semiconductor chips to be mounted increases, there is a demand for thinning of printed wiring boards, and there is a demand for efficient production of printed wiring boards with such fine thin-line structures.

[0003] For example, Patent Document 1 discloses a method in which the surface of a metal foil carrying a catalyst material is bonded to a substrate of a circuit board, and then the metal foil is removed and the catalyst material is laminated on the substrate. A printed wiring board having a circuit pattern is efficiently obtained by further copper plating on the catalyst material laminated on the substrate and performing pattern processing. In this method, if the adhesion between the copper plating layer and the substrate is weak during pattern processing for forming a circuit, the copper plating layer peels off during processing, leading to a decrease in yield. In Patent Document 1, the unevenness provided on the metal foil is transferred to the surface of the substrate, and the adhesion between the copper plating layer and the substrate is improved by the anchor effect of the unevenness. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 163440 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in applications requiring high frequency characteristics, there is a skin effect in which the electrical signals passing through the circuit are concentrated closer to the surface. This requires high smoothness at the interface between the copper plating layer forming the circuit and the substrate. In other words, the technology of Patent Document 1 has a problem in that, while it is necessary to provide irregularities at the interface to improve adhesion, it is necessary to ensure high smoothness at the interface to improve high frequency characteristics, and there is a trade-off between the two.

[0006] Therefore, an object of the present disclosure is to provide a material for printed wiring boards that can provide a printed wiring board having sufficient adhesive strength at the interface between a copper plating layer and a substrate without forming unevenness at the interface, and a method for manufacturing a printed wiring board using the material for printed wiring boards. [Means for solving the problem]

[0007] Means for Solving the Problems The inventors of the present application have discovered through extensive research that when a printed wiring board is manufactured using a material for printed wiring boards, if an adhesive layer containing a specific polyimide resin is applied to the interface between a copper plating layer and a substrate, sufficient adhesion can be ensured without providing unevenness at the interface.

[0008] That is, one embodiment of the material for printed wiring boards disclosed herein comprises at least a catalyst layer and an adhesive layer containing a polyimide resin laminated in this order on at least one surface of a metal foil, and the polyimide resin is formed by copolymerizing an acid dianhydride including a bisphenol diether type acid dianhydride (sometimes referred to as a "specific acid dianhydride" in this specification) with a diamine compound. Effect of the Invention

[0009] A printed wiring board is obtained by bonding the adhesive layer of the material for printed wiring boards of the present disclosure to a substrate, removing the metal foil, and copper plating the exposed catalyst layer for patterning. In the obtained printed wiring board, an adhesive layer containing the above-mentioned polyimide resin is formed at the interface between the copper plating layer and the substrate. Then, chemical bonds are formed between the copper plating layer and the polyimide resin of the adhesive layer, and between the polyimide resin and the substrate, respectively, so that the copper plating layer and the substrate are adhered with strong adhesive strength. In other words, by using the material for printed wiring boards of the present disclosure, it is not necessary to form irregularities at the interface between the copper plating layer and the substrate to obtain an anchor effect, and a printed wiring board having both high smoothness and high adhesion at the interface can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a material for a printed wiring board. [Diagram 2] FIG. 1 is a flow diagram showing an example of a method for manufacturing a printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. The following description of the preferred embodiments is merely illustrative in nature and is not intended to limit the present disclosure, its application, or its uses.

[0012] <Materials for printed wiring boards and printed wiring boards> As shown in Fig. 1, the material 10 for printed wiring boards according to this embodiment includes a metal foil 11, a catalyst layer 12, and an adhesive layer 13. In detail, the material 10 for printed wiring boards is formed by laminating at least the catalyst layer 12 and an adhesive layer 13 containing a polyimide resin in this order on at least one surface 11a of the metal foil 11. The catalyst layer 12 and the adhesive layer 13 may also be provided on the other surface 11b of the metal foil 11. The material 10 for printed wiring boards may further include a base material 21 laminated on the surface of the adhesive layer 13 on the side where the catalyst layer 12 is not present (see Fig. 2(c)).

[0013] The material 10 for printed wiring boards is a material used in manufacturing a printed wiring board 20 (see FIG. 2(f)). Although details will be described later, the adhesive layer 13 and a substrate 21 for a printed wiring board are bonded together, the metal foil 11 is removed, and the exposed catalyst layer 12 is copper-plated and processed into a circuit pattern shape to obtain the printed wiring board 20. That is, in the present disclosure, the material 10 for printed wiring boards can also be referred to as a material for transferring the catalyst layer 12 and the adhesive layer 13 to the substrate 21 for a printed wiring board.

[0014] The printed wiring board material 10 and the printed wiring board 20 and each of the constituent materials will be described in detail below.

[0015] [Metal foil] The metal foil 11 is a support material that holds the catalyst layer 12 and the adhesive layer 13. The metal foil 11 is removed in the manufacturing process of the printed wiring board 20, and is not included in the final product, the printed wiring board 20. Therefore, the metal foil 11 can also be referred to as a sacrificial transfer foil.

[0016] The type of metal foil 11 is not particularly limited, but for example, aluminum foil, aluminum alloy foil, copper foil, and tin foil having a thickness of 5 μm or more and 200 μm or less can be suitably used.

[0017] Furthermore, surface 11a of metal foil 11 may have projections and recesses for the purpose of improving the adhesive strength between copper plating layer 22 and substrate 21, but this is not essential.

[0018] The surface 11a of the metal foil 11 may be highly smooth from the viewpoint of ensuring excellent high-frequency characteristics in the final product, the printed wiring board. In this case, the surface roughness Ra of the metal foil 11 may be, for example, 0.4 μm or less, and is preferably 0.2 μm or less. The lower limit of the surface roughness Ra of the metal foil 11 is not particularly limited, but a surface roughness of, for example, 6 nm or more can be preferably used.

[0019] In this specification, the term "surface roughness Ra" refers to the arithmetic mean roughness Ra defined in JIS B0601 (1982 edition). When an aluminum foil is used as the metal foil 11, the "surface roughness Ra" of the aluminum foil may be expressed as a value calculated by expanding the arithmetic mean roughness Ra defined in JIS B0601 (1982 edition) three-dimensionally so that it can be applied to a surface.

[0020] When an aluminum foil is used as the metal foil 11, the ratio of the total surface area of ​​the crystallized particles to a predetermined surface area is 2% or less, and the average surface area of ​​each crystallized particle is 2 μm 2 An aluminum foil having a surface roughness Rz of 40 nm or less in a direction perpendicular to the rolling direction and a surface roughness Ra of 10 nm or less may be used (see WO2015 / 019960). Since this aluminum foil has high smoothness, a catalyst layer can be transferred to the substrate in a highly smooth state. That is, by laminating a copper plating layer on this catalyst layer, a printed wiring board having high smoothness at the interface between the copper plating layer and the substrate can be manufactured. The surface roughness Ra and Rz of the aluminum foil can be determined, for example, by a method similar to that described in paragraph 0049 of WO2015 / 019960. That is, the surface shape of the aluminum foil can be observed in a rectangular field of view of a predetermined size, such as 80 μm×80 μm, by using an atomic force microscope (for example, a scanning probe microscope Nanopics1000 manufactured by Seiko Instruments Inc.) by a damping method (non-contact). The inclination of the sample is corrected by a cubic surface automatic inclination correction that finds and fits a curved surface by least squares approximation to the obtained observation results, and the surface roughness Ra and the surface roughness Rz in the transverse direction (TD) perpendicular to the rolling direction are measured. As described above, the surface roughness Ra is a value calculated by expanding the arithmetic mean roughness Ra defined in JIS B0601 (1982 edition) into three dimensions so that it can be applied to the entire observed surface. The surface roughness Rz in the transverse direction (TD) can be measured by the two-dimensional Rz value in any cross section in the transverse direction (TD) within the same field of view using an evaluation method based on JIS B0601 (1982 edition).

[0021] The surface of the metal foil 11 may be highly smooth, but it is not excluded to provide the surface with irregularities. In this case, the surface roughness Ra of the metal foil 11 may exceed 0.4 μm. There is no particular limitation on the method of providing the surface of the metal foil 11 with irregularities, and generally known methods may be used.

[0022] [Catalyst layer] The catalyst layer 12 is a layer containing a catalyst for electroless copper plating, which will be described later.

[0023] The catalyst used in the catalyst layer 12 is not particularly limited, and any generally known catalyst can be used as long as it can form a copper plating layer on the surface. Specifically, for example, at least one selected from the group consisting of palladium, platinum, gold, and copper can be suitably used as the catalyst. More preferably, palladium is used as the catalyst because it is less susceptible to surface oxidation, has high catalytic activity, and can form plating even in small amounts.

[0024] The thickness (lamination amount) of the catalyst layer is not particularly limited either, and can be appropriately selected from the range of 1 nm or more and 1 μm or less.

[0025] [Adhesive layer] The adhesive layer 13 is a layer for improving the adhesion at the interface between the copper plating layer 22 and the substrate 21 in the printed wiring board 20, which is the final product.

[0026] The adhesive layer 13 contains a polyimide resin and any additives.

[0027] (Polyimide resin) The polyimide resin contains a structural unit derived from a specific acid dianhydride.

[0028] In other words, the polyimide resin is formed by copolymerizing (A) an acid dianhydride and (B) a diamine compound, and (A) the acid dianhydride includes (A1) a specific acid dianhydride and any (A2) an acid dianhydride other than the specific acid dianhydride.

[0029] (A) Acid dianhydride The acid dianhydride is not particularly limited as long as it contains the (A1) specific acid dianhydride.

[0030] The acid dianhydride may be composed only of the specific acid dianhydride (A1), or may be composed of the specific acid dianhydride (A1) and an acid dianhydride other than the specific acid dianhydride (A2).

[0031] (A1)Specified acid dianhydride The specific acid dianhydride is a bisphenol diether type acid dianhydride. The bisphenol diether type acid dianhydride is not particularly limited as long as it has a bisphenol diether type structure, and examples thereof include 4,4'-(4,4'-isopropylidenediphenoxy)bis(phthalic anhydride) (hereinafter also referred to as BisDA), 4,4'-(4,4'-methylenediphenoxy)bis(phthalic anhydride), and 4,4'-(4,4'-hexafluoroisopropylidenediphenoxy)bis(phthalic anhydride).

[0032] [ka]

[0033] By having an ether bond group in the bisphenol diether type acid dianhydride, the flexibility of the polyimide resin is improved, and even if the interface between the copper plating layer 22 and the substrate 21 is smooth (even if the surface roughness Ra of the metal foil 11 is small), the effect of improving adhesion due to the anchor effect can be expected. In addition, by having a bisphenol group, the toughness can be improved, and the effect of showing good adhesion even in a thin film can be expected. By having both skeletons, a coating film that is flexible and tough can be obtained, and the effect of further improving adhesion at the interface can be expected.

[0034] In order to obtain a coating film that is flexible and tough and has improved adhesion, the content of the specific acid dianhydride in the total acid dianhydride is preferably 30% by mass or more, more preferably 40% by mass or more, and particularly preferably 50% by mass or more.

[0035] The specific acid dianhydride may be used alone or in combination of two or more kinds.

[0036] (A2) Acid dianhydrides other than specified acid dianhydrides The acid dianhydride other than the specific acid dianhydride is not particularly limited as long as it is an acid dianhydride other than the above-mentioned specific acid dianhydride, and is preferably a tetracarboxylic acid dianhydride.

[0037] Specific examples of acid dianhydrides other than the specific acid dianhydrides include 3,4,3',4'-biphenyltetracarboxylic dianhydride (BPDA), 1,1'-bicyclohexane-3,3',4,4'-tetracarboxylic-3,4:3',4'-dianhydride (H-BPDA), pyromellitic dianhydride (PMDA), 4,4'-oxydiphthalic dianhydride (ODPA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), 5-(2,5-dioxotetrahydrofurfuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, 5-(2,5-dioxotetrahydrofurfuryl)-3-cyclohexene-1,2-dicarboxylic dianhydride, and ethylene glycol bistrimellitic dianhydride. Examples of the dianhydride include 2,2',3,3'-biphenyltetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, and ethylenetetracarboxylic dianhydride (structural formulas of some of the compounds are shown below). These dianhydrides may be used alone or in combination of two or more.

[0038] [ka]

[0039] (B) Diamine compound The diamine compound is an amine compound having two amino groups in the molecule. The diamine compound may be either an aromatic compound or an aliphatic compound, but from the viewpoint of obtaining a polyimide film having high mechanical strength, the diamine compound is preferably an aromatic diamine compound.

[0040] Examples of the aromatic diamine compound include p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 1,5-diaminonaphthalene, 3,3-dimethyl-4,4'-diaminobiphenyl, 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, and 7-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane. ,3,3-Trimethylindan, 4,4'-diaminobenzanilide, 3,5-diamino-3'-trifluoromethylbenzanilide, 3,5-diamino-4'-trifluoromethylbenzanilide, 3,4'-diaminodiphenyl ether, 2,7-diaminofluorene, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-methylene-bis(2-chloroaniline), 2,2',5,5'-tetrachloro-4,4'-diaminobiphenyl, 2,2'-dichloro-4,4'-diamino-5,5'-di Methoxybiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)-biphenyl, 1,3'-bis(3-aminophenoxy)benzene (APBN), 9,9-bis(4-aminophenoxy) aminophenyl)fluorene, 4,4'-(p-phenyleneisopropylidene)bisaniline, 4,4'-(m-phenyleneisopropylidene)bisaniline (Bisaniline-M), 4,4'-(p-phenylenediisopropylidene)bisaniline (BisanilineP), 2,2'-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane, 4,4'-bis[4-(4-amino-2-trifluoromethyl)phenoxy]-octafluorobiphenyl, and the like.

[0041] Among these, it is preferable to adopt an aromatic diamine compound having at least one of an ether bond group and a bisphenol skeleton in the molecule.Specific examples of such aromatic diamine compounds include 4,4'-(m-phenylenediisopropylidene)bisaniline (BisanilineM), 4,4'-(p-phenylenediisopropylidene)bisaniline (BisanilineP), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 1,4-bis(4-aminophenoxy)benzene, 1,3'-bis(3-aminophenoxy)benzene (APBN), etc.More preferable are aromatic diamine compounds having both an ether bond group and a bisphenol skeleton in the molecule, and specific examples thereof include (2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP)).

[0042] These aromatic diamine compounds may be used alone or in combination of two or more.

[0043] The polyimide resin is preferably a urethane-modified polyimide resin (also referred to as a "specific polyimide resin" in this specification). More specifically, it is preferably a urethane-modified polyimide resin obtained by copolymerizing an NCO-terminated urethane prepolymer with an acid dianhydride and a diamine compound. By using the specific polyimide resin in the adhesive layer, higher adhesive strength can be obtained at the interface between the copper plating layer 22 and the substrate 21. The polyimide resin may be a mixture of the specific polyimide resin and a polyimide resin other than the specific polyimide resin. In this case, the content of the specific polyimide resin in the polyimide resin is not particularly limited, but may be, for example, 50% by mass or more.

[0044] The adhesive layer 13 may be composed of only polyimide resin, or may contain additives other than polyimide resin. Specific examples of additives include at least one adhesion-imparting additive selected from the group consisting of aminosilanes, epoxysilanes, and triazines. By adding such additives to the polyimide resin, it is possible to obtain a higher adhesive strength at the interface between the copper plating layer 22 and the substrate 21. The content of the additive in the adhesive layer 13 is not particularly limited, but is preferably 0.1 parts by mass or more and 10 parts by mass or less, and more preferably 0.5 parts by mass or more and 2 parts by mass or less, relative to 100 parts by mass of the polyimide resin. By setting the amount of additive added within the above range, it is possible to obtain a high adhesive strength between the copper plating layer and the substrate.

[0045] The content of the polyimide resin in the adhesive layer 13 is preferably 90% by mass or more, and more preferably 98% by mass or more.

[0046] The method for producing the polyimide resin is not particularly limited, and any conventionally known production method can be used. Specific examples include a thermal imidization method in which the polyimide resin is thermally dehydrated and ring-closed, and a chemical imidization method in which a dehydrating agent is used.

[0047] (imide group concentration) The imide group concentration of the polyimide resin is preferably 8% or more and 26% or less, more preferably 8.8% or more and 21.1% or less. If the imide group concentration is less than 8%, the heat resistance inherent to polyimide may be deteriorated. If the imide group concentration is more than 26%, the adhesive strength between the copper plating layer and the substrate may be low, and the copper plating layer may peel off.

[0048] The imide group concentration here is defined by the following formula (1).

[0049] Imide group concentration = (molecular weight of imide group portion: 70.03) ÷ (molecular weight of polyimide repeating unit) × 100 (1) In formula (1), the molecular weight of the imide group portion is the molecular weight of the (-CO-N-CO-) portion contained in the repeating unit of the polyimide. The molecular weight per imide group is 70.03.

[0050] The molecular weight of a repeating unit of a polyimide is the molecular weight of the portion derived from the acid dianhydride and the diamine compound that constitute one repeating unit.

[0051] When a polyimide contains a plurality of repeating units, the imide group concentration of each repeating unit is determined, and then the values ​​obtained by multiplying the imide group concentration of each repeating unit by the content ratio of each repeating unit are summed to obtain the imide group concentration of the polyimide.

[0052] (Weight average molecular weight) The weight-average molecular weight of the polyimide resin is not intended to be limited, but may be, for example, 5,000 to 1,000,000, and preferably 10,000 to 500,000. If the weight-average molecular weight is less than the lower limit, the adhesive layer tends to become brittle, and there is a risk that sufficient adhesive strength between the copper plating layer and the substrate cannot be secured. On the other hand, if the weight-average molecular weight exceeds the upper limit, there is a risk that the solubility in the solvent decreases, and the coatability decreases.

[0053] The weight average molecular weight of the polyimide resin can be measured by a commonly known method such as gel permeation chromatography (GPC).

[0054] [Base material] The substrate 21 is a supporting material that serves as the base of the printed wiring board 20, holds the copper plating layer 22, and imparts stiffness and strength to the printed wiring board 20.

[0055] The substrate 21 may or may not be included in the material 10 for printed wiring boards. That is, the material 10 for printed wiring boards can be distributed without including the substrate 21. In this case, the printed wiring board manufacturer can manufacture the printed wiring board 20 by bonding the material 10 for printed wiring boards and a desired substrate 21 together, removing the metal foil 11, and laminating the copper plating layer 22. The material 10 for printed wiring boards can also be distributed in a state including the substrate 21. In this case, the printed wiring board manufacturer can manufacture the printed wiring board by removing the metal foil 11 and laminating the copper plating layer 22.

[0056] The substrate 21 can be appropriately selected depending on the type of semiconductor to be mounted and the application of the printed wiring board 20 as a final product, and the material and size thereof are not limited. Specifically, the material of the substrate 21 can be at least one selected from the group consisting of ceramics, resin, glass, paper, and metal with an insulating layer on the surface. Resin is more preferable, and glass epoxy resin is particularly preferable from the viewpoints of strength, insulation, and processability. The thickness of the substrate 21 is also not particularly limited, and a substrate having a thickness of 10 μm or more and 10 mm or less can be preferably used, for example.

[0057] [Copper plating layer] The copper plating layer 22 serves as a conductor in the printed wiring board 20, and plays the role of wiring that wraps around the pins (terminals) of the semiconductor so that they can be connected to external connection wiring or terminals when the semiconductor is mounted. Since the copper plating layer 22 is formed on the catalyst layer 12, it is laminated over the entire surface of the copper plating layer 22, but is processed into a circuit pattern shape by etching or the like. In other words, the copper plating layer is a layer that is formed into a circuit pattern shape over the entire surface or a part of the catalyst layer and is laminated on the catalyst layer 12.

[0058] As a method for forming the copper plating layer 22, a generally known method can be adopted, but it is preferable to first form a copper plating layer by electroless copper plating, and then thicken the copper plating layer by electrolytic copper plating to obtain a copper plating layer 22 of the desired thickness.

[0059] The thickness of the copper plating layer 22 is not particularly limited, and can be, for example, in the range of 10 nm or more and 100,000 nm or less.

[0060] [Adhesion at the interface between the copper plating layer and the substrate] In the printed wiring board 20, the peel strength measured by the method described below is preferably 1.00 lbf / in or more, more preferably 2.00 lbf / in or more, and particularly preferably 5.00 lbf / in or more.

[0061] <Manufacturing method for printed wiring board> A method for producing a printed wiring board 20 using the printed wiring board material 10 will be described. Note that, although the following description will be given taking as an example a case where the printed wiring board material 10 does not include a base material 21, this is not intended to be limiting.

[0062] As shown in FIG. 2, the method for manufacturing a printed wiring board of the present disclosure includes, in this order, a step of preparing a material 10 for a printed wiring board, a step of bonding an adhesive layer 13 in the material 10 for a printed wiring board and a base material 21 opposite each other, a step of removing the metal foil 11 from the material 10 for a printed wiring board to expose a surface 12b of the catalyst layer 12 on which the adhesive layer 13 is not provided, a step of laminating a copper plating layer 22 on the surface 12b, and, although not shown in FIG. 2, a step of processing the copper plating layer 22 into a circuit pattern shape as necessary.

[0063] [Process for preparing materials for printed wiring boards] As shown in (a) and (b) of Figures 2, in the process of preparing a material 10 for a printed wiring board, a catalyst layer 12 and an adhesive layer 13 containing a polyimide resin are formed in that order on at least one surface 11a of a metal foil 11.

[0064] The formation of the catalyst layer 12 is not particularly limited, and can be performed by a generally known method such as a wet method such as a catalyst-accelerator method, or a dry method such as a sputtering method or a vapor deposition method. Specifically, for example, in the case of a wet method, a catalyst solution is applied to at least one surface 11a of the metal foil 11 using a bar coater, gravure, slot die, inkjet, spin coating, screen printing, dip coating, or the like, and the catalyst layer 12 is obtained through necessary post-treatment. In the dry method, a layer of a catalyst metal is directly formed on the metal foil 11 to obtain the catalyst layer 12.

[0065] The adhesive layer 13 can be formed, for example, by the following method. That is, a resin solution obtained by dissolving a polyimide resin in a solvent is applied onto the metal foil 11 after the formation of the catalyst layer 12, using a bar coater, gravure, slot die, inkjet, spin coating, screen printing, dip coating, or the like. Thereafter, the solvent is removed by performing a heat treatment in an air atmosphere at a temperature suitable for the solvent used.

[0066] It is not necessary to provide the surface of the metal foil 11 with irregularities. However, if irregularities are to be provided, this can be achieved by subjecting the surface of the metal foil 11 to a roughening treatment or the like before forming the catalyst layer 12.

[0067] [Step of bonding the adhesive layer and the substrate facing each other] 2(c), the adhesive layer 13 and the substrate 21 are laminated facing each other to obtain a structure in which the catalyst layer 12, the adhesive layer 13, and the substrate 21 are laminated in this order on the metal foil 11.

[0068] There is no particular limitation on the method for bonding the adhesive layer 13 and the base material 21, and any commonly known method may be used. Specifically, for example, when bonding the adhesive layer 13 and the base material 21, heating may be performed or pressure (tension) may be applied.

[0069] For example, by bonding the adhesive layer 13 and the substrate 21 together while heating them in the range of 120°C to 300°C, the two can be bonded more closely. More specifically, the adhesive layer 13 and the substrate 21 have improved fluidity upon heating, and their shapes change so as to fill gaps in accordance with the surface shapes of the metal foil 11 and catalyst layer 12 that are in contact with them. When the fluidity is subsequently lost due to a decrease in temperature, the substrate 21 is in a state in which the surface shapes of the metal foil 11 and catalyst layer 12 are transferred thereto.

[0070] Furthermore, when bonding the adhesive layer 13 and the base material 21 together, a pressure of 0.2 MPa to 10 MPa depending on the type of base material 21 can be applied to bond the two more closely.

[0071] Either heating or pressing may be performed, or both may be performed. These treatments may be performed, for example, using a known heat press device. Furthermore, the heat press may be performed under a reduced pressure atmosphere.

[0072] In addition, polyimide resin has higher heat resistance than other thermosetting resins such as epoxy resin, so it can be subjected to high-temperature hot pressing. If a resin with low heat resistance is used, the resin layer may flow and the catalyst in the catalyst layer may diffuse into the resin layer, but by using a polyimide resin with high heat resistance, the catalyst layer and adhesive layer can be maintained as designed. In addition, while other thermosetting resins such as epoxy resins cause blocking, polyimide resin has high blocking resistance and allows the production of printed wiring boards as designed.

[0073] [Step of removing the metal foil to expose the surface of the catalyst layer] 2(d), the metal foil 11 is removed from the structure obtained as described above. Thus, the surface 12b of the catalyst layer 12 on which the adhesive layer 13 is not provided (the surface of the catalyst layer 12 opposite to the surface on which the adhesive layer 13 is laminated) is exposed. This results in a first intermediate product 20A of the printed wiring board 20 in which the catalyst layer 12, the adhesive layer 13, and the base material 21 are laminated in this order.

[0074] The method for removing the metal foil 11 is not particularly limited, and a generally known method can be used. Specifically, for example, a method in which an etching solution is applied to or impregnated into the metal foil 11, and the metal foil 11 is etched and removed is preferably used. When the metal foil 11 is an aluminum foil or an aluminum alloy foil, for example, hydrochloric acid or an aqueous solution of sodium hydroxide can be used as the etching solution.

[0075] [Process of laminating copper plating layer] 2(e) and (f), copper plating is applied to the exposed surface 12b of the catalyst layer 12 to form a copper plating layer 22. Specifically, for example, a copper plating layer having a thickness of 1 μm or less is laminated on the catalyst layer 12 by electroless copper plating, and then an electrolytic copper plating layer having a thickness of 5 μm to 100 μm is formed by electrolytic copper plating to make it a thick film. This forms a conductor layer that is uniform, smooth, and has good electrical conductivity, i.e., low electrical resistance and excellent high-frequency characteristics. In this way, a second intermediate product 20B of a printed wiring board is obtained in which the copper plating layer 22, catalyst layer 12, adhesive layer 13, and base material 21 are laminated in this order.

[0076] [Processing the copper plating layer into a circuit pattern] 2, the copper plating layer 22 laminated over the entire surface 12b of the catalyst layer 12 is processed into a circuit pattern shape, thereby obtaining the final product, the printed wiring board 20.

[0077] The method for processing the copper plating layer 22 into a circuit pattern shape is not particularly limited, and a generally known method such as a lithography method can be used. For example, in the lithography method, a resist ink is applied in the shape of a circuit pattern to the surface of the copper plating layer 22 on the side on which the catalyst layer 12 is not provided, and then an etching solution is applied or impregnated to dissolve the copper plating layer 22 in the area where the resist ink is not applied, thereby leaving the copper plating layer 22 in the shape of a circuit pattern.

[0078] The shape of the circuit pattern is not particularly limited, and a shape appropriately designed according to the shape of the semiconductor, the number of terminals, and the number and shape of the external terminals can be adopted.

[0079] In the printed wiring board 20 manufactured by the above steps, chemical bonds are formed between the copper plating layer 22 and the polyimide resin of the adhesive layer 13, and between the polyimide resin and the substrate 21. As a result, the copper plating layer 22 and the substrate 21 adhere to each other with strong adhesive strength. In other words, by using the printed wiring board material 10 of the present disclosure, it is not necessary to form irregularities at the interface between the copper plating layer 22 and the substrate 21, and a printed wiring board having both high smoothness and high adhesion at the interface can be obtained. EXAMPLES

[0080] Next, specific examples will be described.

[0081] Polyimide resin solutions A to E of Production Examples 1 to 5 shown in Table 1 were prepared, and samples of printed wiring boards of Examples 1 to 14 and Comparative Examples 1 to 4 were produced.

[0082] [Table 1]

[0083] <Production example of polyimide resin> (Production Example 1) In a 500mL separable four-neck flask equipped with a stainless steel anchor stirrer, nitrogen inlet tube, and Dean-Stark apparatus, 0.08 mol of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride (BisDA), 0.08 mol of 3,4,3',4'-biphenyltetracarboxylic dianhydride (BPDA), 0.16 mol of 1,3'-bis(3-aminophenoxy)benzene (APBN), 150.00 g of N-methyl-2-pyrrolidone (NMP), 2.38 g of pyridine, and 50 g of toluene were charged, and the reaction system was replaced with nitrogen, and then the reaction was carried out at 180°C for 6 hours under a nitrogen stream. The water generated by the reaction was distilled out of the reaction system. After the reaction was completed, the system was cooled to 120°C, and 250.00 g of NMP was added to obtain a polyimide resin solution A with a concentration of 20% by mass. The imide group concentration of the polyimide resin contained in the polyimide resin solution A, calculated by the above-mentioned method, was 21.1%.

[0084] (Production Example 2) Except for replacing the acid dianhydride with 0.15 mol of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride (BisDA) and the diamine with 0.15 mol of 4,4'-(p-phenylenediisopropylidene)bisaniline (BisanilineP), synthesis was performed in the same manner as in Production Example 1 to obtain a 20 mass% polyimide resin solution B. The imide group concentration of the polyimide resin contained in polyimide resin solution B calculated by the above method was 16.9%.

[0085] (Production Example 3) Except for changing the acid dianhydride to 0.11 mol of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride (BisDA), changing the diamine to 0.11 mol of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), and changing the solvent to methyl benzoate, synthesis was performed in the same manner as in Production Example 1 to obtain a 20 mass% polyimide resin solution C. The imide group concentration of the polyimide resin contained in the polyimide resin solution C calculated by the above-mentioned method was 15.6%.

[0086] (Production Example 4) Into an apparatus similar to that of Production Example 1, 0.02 mol of an NCO-terminated urethane prepolymer composed of polycarbonate diol (PCD) and diphenylmethane diisocyanate (MDI), 0.06 mol of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride (BisDA), and 156.54 g of methyl benzoate were added, and the reaction was carried out for 1.5 hours while heating and stirring at 140°C.

[0087] Then, 0.04 mol of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) and 76.32 g of methyl benzoate were added, and the mixture was reacted for 5 hours while being heated and stirred at 180°C. Water generated by the reaction was distilled out of the reaction system. After the reaction was completed, the mixture was cooled to 120°C, and 166.33 g of methyl benzoate was added to obtain a 20% by mass polyimide resin solution D. The imide group concentration of the polyimide resin contained in the polyimide resin solution D calculated by the above-mentioned method was 8.8%.

[0088] (Production Example 5) Into an apparatus similar to that used in Production Example 1, 0.18 mol of 4,4'-oxydiphthalic dianhydride (ODPA), 0.13 mol of diethyltoluenediamine (DETDA), 138.90 g of NMP, 4.26 g of pyridine, and 50 g of toluene were charged, and the reaction system was replaced with nitrogen, and then the reaction was carried out at 180°C for 2 hours under a nitrogen stream.

[0089] Next, 0.09 mol of 1,1'-bicyclohexane-3,3',4,4'-tetracarboxylic acid-3,4:3',4'-dianhydride (H-BPDA), 0.13 mol of p-(m-aminophenoxy)aniline (mDADE), and 152.77 g of gamma-butyrolactone (GBL) were added and reacted at 180°C for 6 hours. After the reaction was completed, the mixture was cooled to 120°C, and 83.33 g of GBL was added to obtain a polyimide resin solution E with a concentration of 25% by mass. The imide group concentration of the polyimide resin contained in the polyimide resin solution E calculated by the above method was 30.3%.

[0090] <Examples and Comparative Examples> Example 1 A palladium-containing liquid (Averatek, LMI) was coated on the surface of an aluminum foil (Toyo Aluminum, 1N30, thickness 35 μm, surface roughness Ra 0.2 μm) and heated to laminate a palladium-based catalyst layer on the aluminum foil. Polyimide resin solution A of Production Example 1 was applied to this palladium-based catalyst layer at a dry weight of 0.5 g / m 2 The solvent was then removed by heat treatment at 180°C for 3 minutes, yielding a material for printed wiring boards with a polyimide resin-containing adhesive layer, palladium-based catalyst layer, and aluminum foil.

[0091] The adhesive layer surface of this printed wiring board material and a glass epoxy resin substrate (manufactured by ISOLA, thickness 0.2 μm) were bonded together using a heat press under the conditions of 180 ° C., 80 minutes, and 0.35 MPa to produce a laminate of "substrate / adhesive layer containing polyimide resin / palladium-based catalyst layer / aluminum foil". Next, this laminate was immersed in a hydrogen chloride aqueous solution to dissolve and remove the aluminum foil, resulting in a laminate of "substrate / adhesive layer containing polyimide resin / palladium-based catalyst layer" (intermediate product 20A). Next, electroless copper plating was performed on this laminate to produce a laminate of "substrate / adhesive layer containing polyimide resin / palladium-based catalyst layer / copper plating layer (thickness 1 μm or less)". Further, copper electroplating was performed to obtain a laminate of "substrate / adhesive layer containing polyimide resin / palladium-based catalyst layer / copper plating layer (thickness 35 μm)" (intermediate product 20B).

[0092] For simplicity, the copper plating layer was not processed into a circuit pattern shape, but was used as it was for the printed wiring board sample.

[0093] The obtained sample was heat-treated at 80°C for 12 hours, then cut into 1 cm width, and the peel strength of the interface between the copper plating layer and the substrate was measured. The peel strength was measured by modifying the following part from 8.1 of JIS C 5012 (1993 edition): the sample was peeled 10 mm at a speed of 100 mm / min, and the convex average load value of the load per unit width (lbf / inch) during this time was extracted. A Strograph manufactured by Toyo Seiki and a 90° peeling jig were used to measure the peel strength. The peel strength of the sample of Example 1 was 1.36 lbf / in.

[0094] Example 2 A sample was prepared and the peel strength was measured in the same manner as in Example 1, except that polyimide resin solution A was replaced with polyimide resin solution B. The peel strength of the sample was 2.86 lbf / in.

[0095] Example 3 A sample was prepared and the peel strength was measured in the same manner as in Example 1, except that polyimide resin solution A was replaced with polyimide resin solution C. The peel strength of the sample was 2.63 lbf / in.

[0096] Example 4 A sample was prepared in the same manner as in Example 3, except that 1 part by mass of an aminosilane-based adhesion promoter (KBE903 manufactured by Shin-Etsu Chemical Co., Ltd., formula (2)) was added to 100 parts by mass of polyimide resin in the polyimide resin solution C used in Example 3, and the peel strength was measured. The peel strength of the sample was 4.10 lbf / in.

[0097] [ka]

[0098] Example 5 A sample was prepared in the same manner as in Example 3, except that 1 part by mass of an epoxy silane adhesion promoter (KBM403, formula (3) manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 100 parts by mass of polyimide resin in the polyimide resin solution C used in Example 3, and the peel strength was measured. The peel strength of the sample was 3.32 lbf / in.

[0099] [ka]

[0100] Example 6 A sample was prepared in the same manner as in Example 3, except that 1 part by mass of an epoxy silane adhesion promoter (KBM4803, formula (4) manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 100 parts by mass of polyimide resin in the polyimide resin solution C used in Example 3, and the peel strength was measured. The peel strength of the sample was 2.87 lbf / in.

[0101] [ka]

[0102] Example 7 A sample was prepared in the same manner as in Example 3, except that 1 part by mass of a triazine-based adhesion-imparting additive (Starfine F-10, Formula (5) manufactured by Nissan Chemical Industries, Ltd.) was added to 100 parts by mass of polyimide resin in the polyimide resin solution C used in Example 3, and the peel strength was measured. The peel strength of the sample was 2.86 lbf / in.

[0103] [ka]

[0104] Example 8 A sample was prepared in the same manner as in Example 3, except that 1 part by mass of a triazine-containing adhesion-imparting additive (VD-3, formula (6) manufactured by Shikoku Chemical Industry Co., Ltd.) was added to 100 parts by mass of polyimide resin in the polyimide resin solution C used in Example 3, and the peel strength was measured. The peel strength of the sample was 3.79 lbf / in.

[0105] [ka]

[0106] Example 9 A sample was prepared in the same manner as in Example 3, except that 1 part by mass of a triazine-containing adhesion-imparting additive (VD-5, formula (7) manufactured by Shikoku Chemical Industry Co., Ltd.) was added to 100 parts by mass of polyimide resin in the polyimide resin solution C used in Example 3, and the peel strength was measured. The peel strength of the sample was 5.34 lbf / in.

[0107] [ka]

[0108] Example 10 A sample was prepared and the peel strength was measured in the same manner as in Example 1, except that polyimide resin solution A was replaced with polyimide resin solution D. The peel strength of the sample was 3.86 lbf / in.

[0109] Example 11 A sample was prepared in the same manner as in Example 10, except that 1 part by mass of an epoxy silane adhesion promoter (KBM403 manufactured by Shin-Etsu Chemical Co., Ltd., formula (3) in Example 5) was added to 100 parts by mass of polyimide resin in the polyimide resin solution D used in Example 10, and the peel strength was measured. The peel strength of the sample was 5.33 lbf / in.

[0110] Example 12 A sample was prepared in the same manner as in Example 10, except that 1 part by mass of a triazine-based adhesion-imparting additive (VD-5 manufactured by Shikoku Chemical Industry Co., Ltd., formula (7) in Example 9) was added to 100 parts by mass of polyimide resin in the polyimide resin solution D used in Example 10, and the peel strength was measured. The peel strength of the sample was 5.43 lbf / in.

[0111] Example 13 The aluminum foil is then subjected to a test so that the ratio of the total surface area of ​​the crystallized particles present in a predetermined surface area is 2% or less, and the average surface area of ​​each crystallized particle is 2 μm 2 A sample was prepared in the same manner as in Example 1, except that an aluminum foil (manufactured by Toyo Aluminum, thickness 11 μm, product name "Laxal", surface roughness Ra 7 nm) having a surface roughness Rz of 40 nm or less in the direction perpendicular to the rolling direction and a surface roughness Ra of 10 nm or less was used, and polyimide resin solution A was replaced with polyimide resin solution C, and the peel strength was measured. The peel strength of the sample was 1.15 lbf / in.

[0112] Example 14 The aluminum foil is then subjected to a test so that the ratio of the total surface area of ​​the crystallized particles present in a predetermined surface area is 2% or less, and the average surface area of ​​each crystallized particle is 2 μm 2 A sample was prepared in the same manner as in Example 1, except that an aluminum foil (manufactured by Toyo Aluminum, thickness 11 μm, product name "Laxal", surface roughness Ra 7 nm) having a surface roughness Rz of 40 nm or less in the direction perpendicular to the rolling direction and a surface roughness Ra of 10 nm or less was used, and polyimide resin solution A was replaced with urethane-modified polyimide resin solution D, and the peel strength was measured. The peel strength of the sample was 2.58 lbf / in.

[0113] Comparative Example 1 The surface of an aluminum foil (manufactured by Toyo Aluminum Co., Ltd., 1N30, thickness 11 μm) was coated with a palladium-containing liquid, and heated to laminate a palladium-based catalyst layer on the aluminum foil, thereby obtaining a material for printed wiring boards.

[0114] The catalyst layer of this printed wiring board material and a glass epoxy resin substrate (manufactured by ISOLA, thickness 0.2 μm) were laminated together using a heat press under conditions of 180°C, 80 minutes, and 0.35 MPa to produce a laminate of "substrate / palladium-based catalyst layer / aluminum foil". Next, this laminate was immersed in an aqueous hydrogen chloride solution to dissolve and remove the aluminum foil, resulting in a laminate of "substrate / palladium-based catalyst layer". Next, electroless copper plating was performed on this laminate to produce a "substrate / palladium-based catalyst layer / copper plating layer (thickness 1 μm or less)" laminate. Further, copper electroplating was performed to obtain a "substrate / palladium-based catalyst layer / copper plating layer (thickness 35 μm)" laminate.

[0115] For simplicity, the copper plating layer was not processed into a circuit pattern shape, but was used as it was for the printed wiring board sample.

[0116] The obtained sample was subjected to a heat treatment at 80°C for 12 hours, and then cut into a piece having a width of 1 cm, and the peel strength of the interface between the copper plating layer and the substrate was measured in the same manner as in Example 1. The peel strength was 0.57 lbf / in.

[0117] Comparative Example 2 A sample was prepared and the peel strength was measured in the same manner as in Example 1, except that the polyimide solution A was replaced with the polyimide resin solution E. The peel strength of the sample was 0.90 lbf / in.

[0118] Comparative Example 3 The aluminum foil is then subjected to a test so that the ratio of the total surface area of ​​the crystallized particles present in a predetermined surface area is 2% or less, and the average surface area of ​​each crystallized particle is 2 μm 2 A sample was prepared in the same manner as in Comparative Example 1, except that an aluminum foil (manufactured by Toyo Aluminum, thickness 11 μm, product name "Laxal", surface roughness Ra 7 nm) having a surface roughness Rz of 40 nm or less in the direction perpendicular to the rolling direction and a surface roughness Ra of 10 nm or less was used instead, and the peel strength was measured. The peel strength was 0.32 lbf / in.

[0119] Comparative Example 4 A sample was prepared in the same manner as in Example 1, except that the adhesive layer was formed using a commercially available surface conditioner for plating (Condilyser SP, manufactured by Okuno Chemical Industries Co., Ltd.), and the peel strength was measured. The peel strength was 0.11 lbf / in.

[0120] Based on the peel strength results of each of the above examples and comparative examples, the evaluation results of adhesive strength are shown in Table 1. Here, a peel strength of less than 1.00 lbf / in was rated as × adhesive strength, a peel strength of 1.00 lbf / in or more and less than 2.00 lbf / in was rated as △ adhesive strength, a peel strength of 2.00 lbf / in or more and less than 5.00 lbf / in was rated as ○ adhesive strength, and a peel strength of 5.00 lbf / in or more was rated as ◎ adhesive strength.

[0121] As shown by the above results, a printed wiring board manufactured using the printed wiring board material 10 of the present disclosure has sufficient adhesive strength between the copper plating layer and the substrate, even if unevenness is not necessarily formed at the interface between the copper plating layer and the substrate. [Industrial Applicability]

[0122] The present disclosure is extremely useful because it can provide a material for printed wiring boards that can provide a printed wiring board having sufficient adhesive strength at the interface between a copper plating layer and a substrate without forming unevenness at the interface, and a method for manufacturing a printed wiring board using the material for printed wiring boards. [Explanation of symbols]

[0123] 10. Materials for printed wiring boards 11 Metal foil 11a (one side of metal foil) 12 Catalyst layer 13 Adhesive layer 20 Printed wiring board 21 Base material 22 Copper plating layer

Claims

1. At least a catalyst layer and an adhesive layer containing a polyimide resin are laminated in this order on at least one surface of a metal foil, The polyimide resin is a material for printed wiring boards obtained by copolymerizing an acid dianhydride, including a bisphenol diether type acid dianhydride, with a diamine compound.

2. 2. The material for printed wiring boards according to claim 1, wherein the adhesive layer contains 0.1 parts by mass or more and 10 parts by mass or less of at least one adhesion-imparting additive selected from the group consisting of aminosilanes, epoxysilanes, and triazines, relative to 100 parts by mass of the polyimide resin.

3. The printed wiring board material according to claim 1 , wherein the polyimide resin comprises a urethane-modified polyimide resin.

4. 2. The material for printed wiring boards according to claim 1, wherein the surface roughness Ra of the metal foil is 0.4 μm or less.

5. 2. The material for printed wiring boards according to claim 1, wherein the metal foil is at least one selected from the group consisting of aluminum foil, aluminum alloy foil, copper foil, and tin foil.

6. 2. The material for printed wiring boards according to claim 1, wherein the catalyst layer contains at least one catalyst selected from the group consisting of palladium, platinum, gold, and copper.

7. A step of bonding the adhesive layer of the printed wiring board material according to any one of claims 1 to 6 and a base material so as to face each other; removing the metal foil of the printed wiring board material to expose a surface of the catalyst layer on which the adhesive layer is not provided; laminating a copper plating layer on the surface; processing the copper plating layer into a circuit pattern shape; The method for manufacturing a printed wiring board includes the steps of:

Citation Information

Patent Citations

  • Catalyzed metal foil and uses thereof

    WO2021163440A1